Why teachers do (or do not) implement recommended teaching practices? An application of the theory of planned behavior - Dierendonck, Christophe; Poncelet, Débora; Tinnes-Vigne, Mélanie (Frontiers in Psychology, 2024)
Introduction In Luxembourg, competency-based practices (CBP), differentiated instruction (DI), and formative assessment (FA) have been imposed by the 2009 school law. Referring to the Theory of Planned Behavior (TPB), this study examined factors influencing the implementation of these practices in classrooms. Methods Teachers participated in an online survey assessing their attitudes, subjective norm, perception of behavioral control, intention, and pedagogical practices regarding CBP, DI, or FA. Measurement models were used in structural equation models testing the TPB. Results If the main relationships postulated by the theory were confirmed, some inconstancies were observed depending on the targeted practices. Structural equation TPB models controlling for gender, experience, teaching level, and socio-economic level of the school population explained between 20 and 45% of the variance in teachers’ practices, and between 65 and 75% of the variance in teachers’ intention to use these practices. Discussion The relevance of the TPB for studying teaching practices and implications for professional training are discussed.